ANALISIS PENERAPAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PT BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG BANJARMASIN PERIODE 2017 - 2019 - Hardi, Enny; Susilowati, Pusvita Indria Mei; Sondakh, Antonius Grivaldi; Rahman, Ridha Banu (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
The purpose of this study is to analyze the implementation of Corporate Social Responsibility (CSR) at PT Bank Negara Indonesia (Persero) Tbk Banjarmasin Branch Office for 2017-2019 period. The Global Report Initiative (GRI) G4 was used in this research. This research was a qualitative research with descriptive analysis. The data were obtained from primary and secondary data sources. Data collection techniques used in research were in-depth interviews and literature study. The data analysis technique used was interactive model. The results of this research showed that PT Bank BNI (Persero) Tbk Banjarmasin Branch has recorded and reported the performance of CSR based on GRI G4 indicators in its annual report. The CSR program and CSR reporting disclosure of good and meet the criteria of GRI-G4. It was proved by evaluation or scoring based on these 3 indicators with a value Economic indicator of 84.6%, 65.5% Environment indicator and 76.6% Social Indicator.